Policies, Principles, and Adjudication - Hart, H.L.A. (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
A previously unpublished paper by H.L.A. Hart responding to some of Ronald Dworkin's work, found in Dworkin's archives.
Keywords: Legal Positivism; Adjudication; Hart-Dworkin Debate